Analysis of the Factors that Influence the Mud Farmer Income in Sorkam Barat Subdistrict,Tapanuli Tengah District - Sandry Lanovela Pasaribu; Yusuf Leonard Henuk; Hasnudi .; Iskandar Sembiring; Nurzainah Ginting (Universitas Sumatera Utara, 2018)
Buffalo cattle are one of the commodities that function as a source of animal protein for the community, as savings, additional income, as labor and manure can be used as fertilizer while providing a source of profit / income for farmers.The purpose of the study was to determine the income of mud buffalo farmers and the factors that influence income in the West Sorkam District, Tapanuli Tengah District. The study was conducted in May-August 2018 using primary data. The method used in data collection is interviewing respondents with the Census Method and analyzed with Multiple Linear Regression using SPSS 16 application tools. The results showed that the income of mud buffalo farmers in West Sorkam District was influenced simultaneously by the business scale, breeders' age, farmer experience, the number of family and labor dependents with R square valued at 0.986 (98%). The results of the study showed that the business scale and the number of workers gave a significant influence (P <0.05) on the income of mud buffalo farmers. The income of buffalo farmers in West SorkamSubdistrict is diverse, with the smallest income being Rp. 370,000/ year with a scale of 2 cattle and the largest is Rp. 68,805,000/ year with a livestock business scale of 47 tails.